Analisis Pencegahan Kecurangan Akuntansi Dalam Mengelola Dana Desa Pada Desa Melati Ii Kecamatan Perbaungan - Junita Putri Rajana Harahap; Mhd Dani Habra; yulandari yulandari (Jurnal Riset Akuntansi dan Bisnis, 2021)
This research aims to determine the preventive measures of accounting fraud in managing village funds in Melati II Village, Perbaungan District. The method used in this research uses qualitative research methods. The subjects in this study were all officials of the Melati II Village, Perbaungan District, while the object of the research studied was the prevention of accounting fraud in managing village funds. The results of this study indicate that there are several measures to prevent accounting fraud in managing village funds in Melati Village, Perbaungan District, namely (1) a good internal control system including honesty in work can prevent fraud. (2) Compliance with accounting rules and government is able to prevent and reduce accounting fraud in reporting. (3) Village officials at Melati II implement the principles of good governance. (4) Follow the reporting standards set by the Government, namely government regulations in Permendagri No. 113 of 2014 concerning village financial management.